P341 Perceived risks and psychosocial burden during the COVID-19 pandemic in a large cohort of pediatric and adult patients with Inflammatory Bowel Disease. (27th May 2021) - Koletzko, L; Klucker, E; Le Thi, G; Breiteneicher, S; Rubio-Acero, R; Neuhaus, L; Stark, R; Standl, M; Hölscher, M; Török, H; Koletzko, S; Schwerd, T
Abstract: Background: The COVID-19 pandemic induced restrictions in daily life and anxiety especially in vulnerable parts of the population. We investigated the psycho-social burden of the pandemic and self-perceived risk and harm in a large IBD cohort. Methods: In this monocentric prospective observational study, pediatric (pIBD) and adult patients completed questionnaires related to their IBD (phenotype, disease activity, treatment), comorbidities, demographic and socioeconomic factors, validated tools on Perceived Stress (PSQ) and quality of life (sIBDQ). They judged perception of harm in case of acquiring COVID-19 using ratings from 1 to 7. We used number and type of established conditions for severe COVID-19 outcome to categorize patients in 5 risk groups. SARS-CoV2 antibodies were determined by Elecsys Roche anti-N pan-Ig. All comparisons were made by using t-test, Mann-Whitney-U-test or Chi-square-test where applicable with 2-sided significance levels of 5%. Univariate and multiple logistic regression was performed to determine associations between factors and perceived harm. Results: Between mid-July to mid-October, 504 (62%) of 820 invited IBD patients and 86 pIBD parents completed the survey. Age ranged from 6-85 years, 80% received mono- or combo-therapy with immunomodulator, biologic, JAK-inhibitor or corticosteroids. Remission, mild, moderate and severe disease activity were reported by 46, 39, 12 and 3%, respectively. High harm of potential COVID-19 (>3) was perceived by 75.4%, rates increased with age (p=0.0019). After adjusting for age and gender, high perceived harm was significantly associated with immunosuppressive drugs, number/type of comorbidities, sleep disturbance, unintended gain or loss of weight, higher PSQ and lower sIBDQ scores. PSQ scored lower in males >60 years vs age matched females or younger adults, and in patients in remission vs active disease. PIBD mothers' total PSQ was similar with even higher subscores for demands (P=0.0004) as adults with moderate/severe disease. Compared to pre-pandemic, 58-93% of pIBD decreased physical activities (at home, sports, outdoor) with minor changes in adults. SARS-CoV-2 serology was positive in 0.4% of IBD patients compared to 2% of our city population. Conclusion: Prior to 2nd infection wave, even IBD patients aged <40 years suffer from a high degree of worries, stress and perceived harm for potential COVID-19. Most elderly patients and those with comorbidities adequately estimate their risks. In pIBD, pandemic restrictions substantially impacted on physical activity. The low seropositivity rate indicates high adherence to social distancing or altered immune response due to IBD drugs. Results of the follow up survey in March 21 are underway.